(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
A cross sectional, observational study was carried out on myringoplasty at a tertiary level hospital, with the aims to see the outcome of surgery. The study included 100 myringoplasty in central dry perforations of tubotympanic variety of CSOM. Age range of patients was from 15 years to 45 years; male was 56%.There was insignificant influences of age or sex on success rate. The surgeries were done under either local or general anaesthesia by underlay technique with temporalis fascia as a graft in all cases with different approaches without any significant influences on outcome. Site and size of the perforations had significant effect on surgical outcome. The overall graft take rate was 84%. The mean preoperative and postoperative air conduction threshold in the successful cases were 35.2dB & 24.1dB respectively with a mean audiological improvement of 11.1dB & air bone gap improvement was 12.4dB. Key words: Myringoplasty, outcome. DOI: 10.3329/bjo.v15i2.5054 Bangladesh J Otorhinolaryngol 2009; 15(2): 40-44